The Early Implementation of FFT-CW®, MST-Psychiatric®, and SafeCare® in Australia. (September 2020) - Albers, Bianca; Hateley-Browne, Jessica; Steele, Thomas; Rose, Vanessa; Shlonsky, Aron; Mildon, Robyn
Purpose: In 2017–2018, the state of Victoria, Australia, initiated the implementation of five family and parenting programs within family services. Three—SafeCare®, Functional Family Therapy-Child Welfare®, and Multisystemic Therapy-Psychiatric®—originated in the United States and were supported through overseas intermediary or purveyor organizations (IPOs). This study examines the challenges and barriers faced by service agencies and their staff during the initial implementation of these three research-supported interventions (RSIs). Method: Qualitative data collected among a purposive sample of implementers selected across provider agencies and IPOs were analyzed. Results: IPOs' implementation specialists used a similarly composed sample of N = 31.2 implementation strategies. The early implementation stage was fragile and characterized by three distinct phases. Primary implementation challenges existed in the inner setting, intervention, and individual characteristics. Discussion: To balance the fragility of early implementation and sustain RSI implementation, it is important to immediately supplement overseas IPO support with strong local implementation capacities.